Stereoselectivity and conformational stability of haloalkane dehalogenase DbjA from Bradyrhizobium japonicum USDA110: the effect of pH and temperature - Chaloupkova, Radka; Prokop, Zbynek; Sato, Yukari; Nagata, Yuji; Damborsky, Jiri (The FEBS journal, 2011)
The effect of pH and temperature on structure, stability, activity and enantioselectivity of haloalkane dehalogenase DbjA from Bradyrhizobium japonicum USDA110 was investigated in this study. Conformational changes have been assessed by circular dichroism spectroscopy, functional changes by kinetic analysis, while quaternary structure was studied by gel filtration chromatography. Our study shows that the DbjA enzyme is highly tolerant to pH changes. Its secondary and tertiary structure was not affected by pH in the ranges 5.3-10.3 and 6.2-10.1, respectively. Oligomerization of DbjA was strongly pH-dependent: monomer, dimer, tetramer and a high molecular weight cluster of the enzyme were distinguished in solution at different pH conditions. Moreover, different oligomeric states of DbjA possessed different thermal stabilities. The highest melting temperature (T(m) = 49.1 ± 0.2 °C) was observed at pH 6.5, at which the enzyme occurs in dimeric form. Maximal activity was detected at 50 °C and in the pH interval 7.7-10.4. While pH did not have any effect on enantiodiscriminination of DbjA, temperature significantly altered DbjA enantioselectivity. A decrease in temperature results in significantly enhanced enantioselectivity. The temperature dependence of DbjA enantioselectivity was analysed with 2-bromobutane, 2-bromopentane, methyl 2-bromopropionate and ethyl 2-bromobutyrate, and differential activation parameters Δ(R-S)ΔH and Δ(R-S)ΔS were determined. The thermodynamic analysis revealed that the resolution of β-bromoalkanes was driven by both enthalpic and entropic terms, while the resolution of α-bromoesters was driven mainly by an enthalpic term. Unique catalytic activity and structural stability of DbjA in a broad pH range, combined with high enantioselectivity with particular substrates, make this enzyme a very versatile biocatalyst. Enzyme EC3.8.1.5 haloalkane dehalogenase.
Keywords: Temperature; Enzyme Stability; multimerizace proteinu; denaturace proteinů; Stereoisomerism; Protein Structure, Tertiary; Thermodynamics; terciární struktura proteinů; Hydrogen-Ion Concentration; Hydrolases; sekundární struktura proteinů; Chromatography, Gel; Protein Structure, Secondary; hydrolasy; Bradyrhizobium; Circular Dichroism; koncentrace vodíkových iontů; termodynamika; stabilita enzymů; substrátová specifita; stereoizomerie; konformace proteinů; Substrate Specificity; cirkulární dichroismus; gelová chromatografie; Protein Denaturation; Protein Conformation; teplota; Protein Multimerization